1998
DOI: 10.1002/(sici)1098-2752(1998)18:3<166::aid-micr7>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Venous free flaps for reconstruction of skin defects of the hand

Abstract: Twenty-one cases of skin defects of the hand were treated with venous flaps. According to type, nine flaps were arterialised flaps (A-A), five were (A-V), and seven were (V-V) type. Venous flaps can be used up to 8 x 3 cm in size or even bigger if the number of veins anastomosed is increased. The main advantage of venous flaps is that they can also be used for simultaneous reconstruction of circulation in digits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…With respect to the overall flap success rates, De Lorenzi et al 11 reported a success rate of 92% in 40 cases, Nishi 14 reported a success rate of 88% in 32 cases, and Kanrarci et al 9 reported a success rate of 91% in 21 cases. The authors of the current study obtained a success rate of 89% in 44 cases, showing an outcome similar to that of others with these flaps.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the overall flap success rates, De Lorenzi et al 11 reported a success rate of 92% in 40 cases, Nishi 14 reported a success rate of 88% in 32 cases, and Kanrarci et al 9 reported a success rate of 91% in 21 cases. The authors of the current study obtained a success rate of 89% in 44 cases, showing an outcome similar to that of others with these flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Local flap reconstruction techniques for covering thumb defects are well established, and include homodigital and heterodigital flaps. [3][4][5][6][7] These local flaps are excellent for an instant and easy reconstruction, but drawbacks such as limitations of flap advancement or coverage, flexion contracture of interphalangeal joint, or severe donor site scarring are secret worries of hand surgeons. 4,8 Furthermore, a distal third or a distal half of the thumb lesion requires sensate, durable, and padded soft tissue repair.…”
mentioning
confidence: 99%
“…8 Few flaps available today are comparable to the digital artery flap in terms of thickness, quality, and pliability. While some authors favor venous flaps and perforator-based radial or ulnar forearm free flaps for digital defects in view of their lower donor morbidity, [17][18][19][20][21][22] these flaps are inherently at risk for congestion, swelling, and delayed healing. In this context, the reliable and superior tissue quality of the digital artery free flap offers a definite advantage by allowing early primary healing, with minimal scarring and swelling.…”
Section: Discussionmentioning
confidence: 99%